Examination of the population density and sowing date of different maize genotypes in the Hajdúság region - Máriás, Károly; Pepó, Péter (Acta Agraria Debreceniensis, 2012)
The experiment was carried out 6 km from Debrecen, next to the main road 47 on a homogeneous field on brown forest soil. Five corn hybrids were tested in the trial (DKC 4795, DKC 4995, KWS Kornelius, NK Cobalt, PR37 N01) at three different sowing times (early – 5th April, average – 21st April, late – 10th May). At each sowing time, three different plant densities were applied (modest – 58 500 plants ha-1, average –70 200 plants ha-1, high – 82 300 plants ha-1). The agrotechnics applied in the experiment satisfied the requirements of modern corn cultivation. In the study, the best yield result was achieved with the early sowing time out of the three examined sowing times (11 315 kg ha-1), which was significantly different (LSD5%=495 kg) from that of the average sowing time (10 690 kg ha-1), however, there was no statistically justifiable difference between the yield results of the early and the late sowing times. There was a significant difference also between the average and late sowing time. Our results indicate that the different sowing times resulted in a different flowering times. Consequently, the stands of early and late sowing time reached this critical stadium of growth under proper climatic circumstances (precipitation: 39 mm and 136 mm, average temperature at flowering: 18.1 oC and 20.3 oC), while flowering in the case of the average sowing time of 21st April was in the first half of July and the average temperature at flowering was warmer (23.2 oC) with only 10 mm precipitation. In the experiment, the plant density response was also examined. According to the measured data, four of the five hybrids responded badly to the increasing plant density. We found that the plant density of 58 500 plant ha-1 gave the largest yield results (DKC 4995 11 794 kg ha-1 – NK Cobalt 10 998 kg ha-1, average of five hybrids: 11 430 kg ha-1), while the lowest yields were obtained at the plant density of 82 300 plant ha-1 (KWS Kornelius 11 037 kg ha-1 – NK Cobalt 10 019 kg ha-1, average of five hybrids 10 720 kg ha-1). The difference between the two plant densities was significant (LSD5%=494 kg), however, the 70 200 plant ha-1 plant density did not show any statistical difference from neither the 58 500 ha-1 nor from the 82 300 plant ha-1 stands. When examining the data of the hybrids separately, we found that there was a significant difference between the average yield of the lowest and highest plant densities only in the case of three (DKC 4795, DKC 4995, NK Cobalt) out of the five hybrids (DKC 4795: 11 757 kg ha-1 – 10 857 ha-1 where LSD5% =816 kg; DKC 4995: 11 794 kg ha-1 – 10 738 kg ha-1 where LSD5%=853kg; NK Cobalt: 10 998 kg ha-1 – 10 019 kg ha-1 where LSD5%=630 kg ha-1), while a significant difference between the second and third plant densities was observed only in one case (DKC 4995: 11 726 kg ha-1 – 10 738 ha-1 where LSD5%=853 kg). In all other cases, there was no statistical difference between the different plant densities.